Swamys handbook 2025 (hindi) - Muthuswamy sanjeev Brinda (Chennai Swamy publishers (P) Ltd., 2025)
Ninth hindi edition incorporating latest orders based on Seventh Pay Commission Report . All Allowances including TA are updated with latest orders (Swamy's Personal Organizer appended to the Handbook)
Keywords: Central government rules; Government service rules; Government administration rules